Clinical, microbiologic, and treatment outcomes of dematiaceous fungal keratitis – A retrospective study - Niruban Ganesan; Shivananda Narayana; Joseph Gubert; Namrata K Bhosale; Balagiri Sundar (Indian Journal of Ophthalmology)
Purpose: Dematiaceous fungi, the third most common causative organism of fungal keratitis, constitute 3.5% to 43.5% of fungal keratitis worldwide. Several studies on filamentous fungi (Aspergillus and Fusarium) are available as opposed to that on dematiaceous fungal keratitis. This study aims to describe the profile of dematiaceous fungal keratitis in South India. Methods: This institutional cohort study on culture-proven dematiaceous fungal keratitis was performed in a single ophthalmology referral center in South India for a 6-year period. Records were analyzed for demographic, clinical, microbiological, and treatment outcomes for 3 months from the date of presentation. Results: This study comprised 312 cases involving dematiaceous fungal keratitis (DFK). During the study period, DFK accounted for 10% of microbial keratitis and 24.6% of fungal keratitis cases. The mean (standard deviation) age was 54 (14) years. Males were commonly affected (73.4%). Keratitis was ≤1/3rd depth in 47.8% of cases. Fifty-four cases (17.3%) demonstrated surface pigmentation, and 69 cases (22.1%) had endothelial plaque. Curvularia spp. (99 eyes, 31.7%) was the most common fungal isolate among the speciated fungi. Topical medications resulted in the healing of 63.5% of cases. A total of 193 cases (79%) healed, and 49 cases had to undergo therapeutic penetrating keratoplasty (TPK). Early TPK was performed for 20 cases (40.8%). Seventeen eyes (34.6%) maintained clear grafts at the end of 3 months. Conclusion: In this extensive study on DFK, we report a high incidence of this group of fungal keratitis. We found an excellent healing rate in our cohort of patients.